Curcumin Liposomal Formulations as Potential Therapeutics for Canine Osteoarthritis - Rasool, Akhter (International Journal of Pharmaceutical & Biological Archive, 2024)
Osteoarthritis (OA) is a multifaceted joint disorder affecting various structures, including articular cartilage, peri-articular bone, synovial joint lining, and connective tissues. This degenerative condition manifests as joint pain, stiffness, reduced mobility, and functional decline, impacting both dogs and humans globally. Risk factors include breed predispositions, joint diseases, higher body weight, and age. The current clinical approaches aim at symptom management and disease progression delay, with limited curative methods available. Nanoparticle (NPs)-based drug delivery systems, particularly curcumin liposomal formulations, show promise in OA treatment. Liposomes, lipid-based NPs, provide targeted drug distribution, extended-release, and enhanced retention in affected joints. Curcumin, a tetraterpenoid, exhibits anti-inflammatory, and antioxidant properties. Despite its efficacy, poor oral bioavailability led to the development of curcumin NPs to enhance therapeutic impact. Intra-articular administration of curcumin, especially in the form of curcumin monoglucuronide, addresses challenges associated with low hydrophilicity, demonstrating effectiveness in suppressing cartilage degeneration in OA. While non-encapsulated curcumin exhibits efficacy, its limited bioavailability prompts innovative approaches like curcumin NPs. The combination of curcumin with non-steroidal anti-inflammatory drugs or chondroprotective agents enhances anti-inflammatory effects, minimizing adverse reactions. Studies support curcumin’s multifaceted therapeutic potential, promoting chondrogenic differentiation and inhibiting inflammatory mediators. This comprehensive review provides insights into canine OA treatment, emphasizing curcumin liposomal formulations as a promising avenue for informed decision-making in veterinary practice.